GDPR: A Step Towards a User-centric Internet? - Maciej Sobolewski; Joanna Mazur; Michał Paliński (Intereconomics, 2017)
While the potential empowering impact of the GDPR is huge, we argue that the ambivalent attitudes of users towards data protection, as well as the risk of differentiation of legal practice among member states, can seriously limit the real effects of the privacy reform.
Keywords: 330